Understanding inequality, poverty and wealth policies and prospects - Ridge, Tess. (Bristol Policy, 2008)
At a time when the divide between the wealthy and the disadvantaged is widening, this major textbook provides students with a critical understanding of poverty and social exclusion in relation to wealth, rather than as separate from it.Raising fundamental questions about the organisation of society, social structures and relationships and social justice, the book is split into four main sections exploring key concepts and issues; 'people and place' (poverty and wealth across different groups and situations); the role of the state; and prospects for the future. This is the only textbook to focus on the links between wealth and poverty and contains an edited collection of chapters specially written by a distinguished panel of contributors including Pete Alcock, Daniel Dorling, Mary Shaw, Gill Scott and Jay Ginn. It is designed with the needs of students in mind and includes useful chapter summaries, illustrative boxes and diagrams, and pointers to relevant websites and other sources of further information.This is an essential textbook for level 1/2 undergraduate students studying social policy either as a main subject or as part of their course. It is a core text for level 3/4 specialist modules in this field.
Published in association with the Social Policy Association.
Keywords: Income distribution -Great Britain